(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Among diseases of the endocrine system, hypothyroidism is the second most common after diabetes [1]. The difficulty of diagnosing hypothyroidism lies in the diversity and nonspecificity of symptoms. This is due to the fact that thyroid hormones have an effect on almost all organs and systems. At the same time, the severity of manifestations of thyroid insufficiency can be different and does not always correlate with the severity of laboratory changes [2,4]. In the clinical picture, a patient with hypothyroidism may have multiple symptoms, which makes diagnosis difficult, especially in elderly and multimorbid patients. Patients often experience a predominance of symptoms from one system, and therefore there is a concept of diseases - “masks” of hypothyroidism, the clinical manifestations of which are discussed in this review [3,5,6]. Under the “mask” of hypothyroidism, diastolic hypertension, dyslipidemia, and hydropericardium can occur; chronic constipation, cholelithiasis, polyarthritis, alopecia, onycholysis, depression, dysfunctional uterine bleeding, infertility, anemia, etc. Due to the variety of clinical manifestations, a patient with hypothyroidism may be seen by a doctor of almost any specialty or simultaneously observed by several different specialists. The doctor must remember the likelihood of hypothyroidism in the patient, know the features of damage to organs and systems when thyroid function decreases. It is necessary to ask the patient in detail about concomitant diseases, which will allow one to suspect the presence of hypothyroidism as the cause of a combination of various nosologies[7,8]. hydropericardium; chronic constipation, cholelithiasis, polyarthritis, alopecia, onycholysis, depression, dysfunctional uterine bleeding, infertility, anemia, etc. Due to the variety of clinical manifestations, a patient with hypothyroidism may be seen by a doctor of almost any specialty or simultaneously observed by several different specialists. The doctor must remember the likelihood of hypothyroidism in the patient, know the features of damage to organs and systems when thyroid function decreases. It is necessary to ask the patient in detail about concomitant diseases, which will allow one to suspect the presence of hypothyroidism as the cause of a combination of various nosologies[7,8]. hydropericardium; chronic constipation, cholelithiasis, polyarthritis, alopecia, onycholysis, depression, dysfunctional uterine bleeding, infertility, anemia, etc. Due to the variety of clinical manifestations, a patient with hypothyroidism may be seen by a doctor of almost any specialty or simultaneously observed by several different specialists. The doctor must remember the likelihood of hypothyroidism in the patient, know the features of damage to organs and systems when thyroid function decreases. It is necessary to ask the patient in detail about concomitant diseases, which will allow one to suspect the presence of hypothyroidism as the cause of a combination of various nosologies[7,8]. Due to the variety of clinical manifestations, a patient with hypothyroidism may be seen by a doctor in almost any specialty or simultaneously observed by several different specialists. The doctor must remember the likelihood of hypothyroidism in the patient, know the features of damage to organs and systems when thyroid function decreases. It is necessary to ask the patient in detail about concomitant diseases, which will allow one to suspect the presence of hypothyroidism as the cause of a combination of various nosologies[7,8]. Due to the variety of clinical manifestations, a patient with hypothyroidism may be seen by a doctor in almost any specialty or simultaneously observed by several different specialists. The doctor must remember the likelihood of hypothyroidism in the patient, know the features of damage to organs and systems when thyroid function decreases. It is necessary to ask the patient in detail about concomitant diseases, which will allow one to suspect the presence of hypothyroidism as the cause of a combination of various nosologies[7,8].